Pengaruh suhu sintering pada penyerapan gelombang mikro nanokomposit NiFe2O 4 / PVDF untuk material penyerap radar (Sintering temperature effect on microwave absorption of NiFe2O4 / PVDF nanocomposite for radar-absorbent materials) - Moulia Fadhilah; - Ramli; - Gusnedi; - Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2019)
Synthesis ofoNiFe2O4/PVDF nanocomposite with sintering temperature variations of 2500C, 280, 3000C, 3500C, 4500C has been done with the solgel method for microwave absorbing material (RAM).This material is to reduce reflections or absorb microwaves, so objects coated with RAM are not detected by Radio Detection and Ranging (RADAR). In making nanocomposite NiFe2O4 / PVDF, it includes the making of Fe3O4 precursor solution using iron sand, making NiFe2O4 solution, making NiFe2O4 / PVDF nanocomposite, printing, and sintering. The samples were characterized by XRD. FTIR and VNA. For the analysis of microwave absorption ability as measured by the Vector Network Analyzerr(VNA), and then maximum Reflection Loss (RL) number was obtained at theesintering temperature of 2800C at -27.5767 dB at aafrequency off11.20 GHz which the X-Band region with microwaveeabsorption in coefficient amounting to 0.0417989142. Nanocomposite NiFe2O4 / PVDF can absorb microwaves 96% at a frequency of 11.20 GHz. So, NiFe2O4/PVDF nanocomposite is suitable for Absorbing Radar Material